(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
Pisang tanduk (Musa paradisiaca L.) is a plant with very abundant fruit. Banana horns are characterized by a fruit length that is longer than other types of banana, ranging from 25-30 cm. However, banana productivity is still very low due to the Banana Bunchy Top Virus (BBTV) disease. This research in 12 regencies/cities in the South Sumatra region. This research applies a purposive sampling method by determining the coordinates of the horn banana plantation and photographing them with a timestamp camera. The results of this field practice show that the symptoms of BBTV attacks are characterized by the presence of small/dwarf banana trees with hardened and straight/erect leaf veins facing the top and changing color to yellowish. The district/city with the largest percentage of attacks was in the Palembang area with 69% of the total number of bananas found. From this field practice it can be concluded that the distribution of horn bananas in the South Sumatra region is not evenly distributed. Communities should reduce the use of pesticides and continue to carry out land sanitation on banana plantations to reduce the population of weeds associated with pisang tanduk.